论“她综艺”中的女性形象建构 —— 以《乘风破浪的姐姐》为例 = The construction of female images in “She Variety Show”: a case study of "Sisters Who Make Waves" - 符馨丹 Fu, Xindan (Nanyang Technological University, 2024)
随着女性在社会中地位的提高，她们的需求也越来越受到关注。在综艺节目领域，女性观众的重要性日益凸显，因此有更多以女性为主要受众对象的综艺节目一一面世，成为了开发综艺市场的一个新方向。“她综艺”的兴起，引来了新的一波关于“女性主义”课题的浪潮，成为大众探讨女性身份与形象的炙热话题。其中《乘风破浪的姐姐》作为中国第一部逆龄女团综艺，它不仅有着定位上的创新，也符合社会对中龄女性的宽容和期待。本文将以此综艺为例，基于女性主义理论，通过剖析节目中的影视符号与影视语言等一系列元素来探讨其中所建构的女性形象,从而对节目所输出的社会性别意识进行批判与反思。As women's social status rises, attention has been drawn to women's demands. In the entertainment field, the importance of female audience in variety shows is becoming more and more prominent, and "She variety show" has become a new field for variety shows to capture the female market. The rise of “She variety show” has sparked a new wave of discussions on feminism issues, becoming a hot topic for the public to explore women's identities and images. As China's first age-defying female group variety show, "Sisters Who Make Waves" is not only innovative in its positioning, but also in line with society's tolerance and expectations towards middle-aged women. This paper will take this variety show as an example, and based on feminist theory, to explore the construction of female images through the analysis of visual and language symbols, thereby reflecting on the societal gender consciousness conveyed by the show.